The Use Of Audio Visual Media In Increasing The Religious Values - Saini Saini; Muhammad Basri (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
ABSTRACT. This study aims to determine the increase in religious values early childhood using audio media visuals at PAUD BUNDA Medan in 2022/2023. This research uses a qualitative approach with descriptive methods. The research subjects were 15 students. Obtaining research data is done by using an observation sheet consisting of data on religious values of Early Childhood. Data collection techniques namely observation, interviews, documentation. Based on the results of data analysis it was concluded that the religious values of Early Childhood can be enhanced by using audiovisual media The development of religious values in early childhood before using audio-visual learning media at PAUD Bunda can be seen the level of development of children's religious values, namely at the pre-action meeting that the development of children's religious values at PAUD Bunda Medan before using audio-visual media found that there were no children who have the development of religious values that are categorized as starting to develop according to expectations. At the first meeting the overall student learning was 77.5%, this was included in the growing category. However, at the second meeting of observation, the child was classified as developing according to expectations, an increase of 85.5%, including in the category of developing according to expectations. At the third meeting, the increase in children's religious values increased by 88.0%, including in the very well developed category, through an assessment of the activity of developing children's religious values, they did not carry out RPPH but led to repetition of material.Keywords: Audio Visual Media, Religious Values  ABSTRAK. Penelitian ini bertujuan untuk mengetahui peningkatan nilai agama anak Usia Dini dengan menggunakan media audio visual di PAUD BUNDA Medan tahun 2022/2023. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian berjumlah 15 orang siswa. Pemerolehan data penelitian dilakukan dengan cara menggunakan lembar observasi yang terdiri dari data nilai-nilai agama Anak Usia Dini. Teknik pengumpulan data yaitu observasi, wawancara, dokumentasi. Berdasarkan hasil analisis data disimpulkan bahwa nilai-nilai agama Anak Usia Dini dapat ditingkatkan dengan menggunakan media audiovisual Perkembangan nilai-nilai agama anak usia dini sebelum digunakan media pembelajaran audio visual di paud bunda dapat diketahui tingkat perkembangan nilai-nilai agama anak yaitu pada pertemuan pra tindakan bahwa perkembangan nilai agama anak di paud bunda medan sebelum menggunakan media audio visual bahwa tidak ditemukan anak yang memiliki perkembangan nilai agama yang dikatagorikan  mulai berkembang sesui harapan. Pada pertemuan pertama belajar siswa keseluruhannya sebesar 77,5% hal ini termasuk pada katagori  mulai berkembang. Namun pada saat  obsevasi pertemuan kedua, anak tergolong berkembang sesui harapan meningkat sebesar 85,5% termasuk pada katagori berkembang sesui harapan. Di pertemuan kegita peningkatan nilai agama anak meningkat sebesar 88,0% termasuk pada kategori berkembang sangat baik, melalui penilaian aktivitas perkembangan nilai agama anak tidak melakukan RPPH namun mengarah pada pengulangan materi.Kata Kunci: Media Audio Visual, Nilai Religius